2005
DOI: 10.1038/sj.npp.1300831
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Pharmacokinetic Interaction between Oxcarbazepine and Lamotrigine

Abstract: Epilepsy and bipolar disorder are commonly treated by combination drug therapy, such as lamotrigine and oxcarbazepine. To ensure the safety of this combination, information on pharmacokinetics and tolerability must be available. The objective of study was to evaluate the pharmacokinetics and tolerability of coadministered lamotrigine and oxcarbazepine in healthy subjects. This randomized, single-blind, parallel-group study comprised three cohorts: lamotrigine (200 mg daily) plus oxcarbazepine (600 mg twice dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…Furthermore the results clears that there were no alterations in basic pharmacokinetic parameters such as the obtained elimination rate constant, elimination t 1/2 and Cl T obtained results were in correlation with those of the results already reported. The data for LMT revealed that the maximum drug concentration obtained was found to be similar to that demonstrated by Theis et al, [10] but the time to peak concentration was at 1h probably this was obtained from large population between 0.5 h and 2.5 h. From early trial phase 3 studies performed, the therapeutic anticonvulsant serum concentration was between 1-4 µg/mL and 3-14 µg/ mL has proven to be quite safe but few [11][12][13] reported that concentration above 12 µg/mL was optimum probably such a high concentration may be required depending upon patients and their side effects. There was a direct relationship between daily dose, plasma level of LMT and analgesic effects, which was previously explained by Lunardi et al [14] Although only a few animals were used per treatment group, the effects seen were consistent across the groups and based on ethical grounds.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore the results clears that there were no alterations in basic pharmacokinetic parameters such as the obtained elimination rate constant, elimination t 1/2 and Cl T obtained results were in correlation with those of the results already reported. The data for LMT revealed that the maximum drug concentration obtained was found to be similar to that demonstrated by Theis et al, [10] but the time to peak concentration was at 1h probably this was obtained from large population between 0.5 h and 2.5 h. From early trial phase 3 studies performed, the therapeutic anticonvulsant serum concentration was between 1-4 µg/mL and 3-14 µg/ mL has proven to be quite safe but few [11][12][13] reported that concentration above 12 µg/mL was optimum probably such a high concentration may be required depending upon patients and their side effects. There was a direct relationship between daily dose, plasma level of LMT and analgesic effects, which was previously explained by Lunardi et al [14] Although only a few animals were used per treatment group, the effects seen were consistent across the groups and based on ethical grounds.…”
Section: Discussionsupporting
confidence: 88%
“…We did not demonstrate a significant effect of OXC on LTG CL, but our sample size was small, with only 10 serum levels among older adults and 8 serum levels in younger adults taking LTG in combination with OXC. Some (May et al., 1999; Weintraub et al., 2005), but not all (Theis et al., 2005), larger prior studies have shown that OXC increases LTG CL modestly (15–30%).…”
Section: Discussionmentioning
confidence: 90%
“…Oxcarbazepine and methsuximide may enhance the metabolism of lamotrigine, resulting in lower serum lamotrigine concentrations (May et al, 1999; Besag et al, 2000; Wellington & Goa, 2001). A lowering effect of oxcarbazepine on serum lamotrigine levels, however, has not been confirmed in all studies (Theis et al, 2005).…”
Section: Relevance Of Tdm For Individual Aedsmentioning
confidence: 99%